Dynamic assessment of RBC‐transfusion dependency improves the prognostic value of the revised‐IPSS in MDS patients. Issue 6 (20th March 2017) - Hiwase, Devendra K.; Singhal, Deepak; Strupp, Corinna; Chhetri, Rakchha; Kutyna, Monika M.; Wee, L. Amilia; Harrison, Peter B.; Nath, Shriram V.; Wickham, Nicholas; Hui, Chi‐Hung; Gray, James X.; Bardy, Peter; et al.
Abstract: RBC‐transfusion dependency (RBC‐TD) is an independent prognostic factor for poor overall survival (OS) in the WHO classification‐based prognostic scoring system (WPSS) for MDS patients. However, WPSS did not include cytopenia, whereas revised International Prognostic Scoring System (IPSS‐R) did not include RBC‐TD. Thus, neither of these prognostic scoring systems incorporates both cytopenia and RBC‐TD. We aimed to test whether RBC‐TD adds prognostic value to the IPSS‐R. We analyzed MDS patients not treated with disease‐modifying therapy, and enrolled in SA‐MDS Registry (derivation cohort; n = 295) and Dusseldorf registry (Germany; validation cohort; n = 113) using time‐dependent Cox proportional regression and serial landmark analyses. In the derivation cohort, RBC‐TD patients had inferior OS compared to RBC transfusion‐independent (RBC‐TI) patients ( P < 0.0001) at 6‐ (18 vs. 64 months), 12‐ (24 vs. 71 months), and 24‐months (40 vs. 87 months). In a Cox proportional regression analysis, RBC‐TD was an independent adverse prognostic marker in addition to age, sex, and IPSS‐R variables ( P < 0.0001). A prognostic index (PI) was derived using these Cox‐proportional regression model variables. In the validation cohort, this PI classified patients into four prognostic groups with significantly different OS ( P < 0.001) as in the derivation cohort. In conclusion, multivariate analysis by Cox proportional hazards regression and serial landmark analyses clearly demonstrates that development of RBC‐TD at any time during the course of MDS is associated with poor OS, independent of IPSS‐R. This study demonstrates that dynamic assessment of RBC‐TD provides additional prognostic value to IPSS‐R and should be included in treatment decision algorithms for MDS patients.